Submandibular gland obstruction caused by an implant-retained lower denture: a report of three cases. Issue 10 (October 2021) - van der Meij, E.H.; Beumer, L.J.; Matthews-Brzozowski, A.; de Visscher, J.G.A.M.
Abstract: The aim of this study was to investigate the role of lower dentures in the development of distally located stenoses of Wharton's duct and to further identify contributing factors to this mechanism. In a database of 352 patients with submandibular gland obstruction, three patients with four obstructed glands with stenosis of the ostium of Wharton's duct suspected to be caused by a lower denture were identified and further retrospectively analysed by studying medical records, operation reports, and clinical photographs. In all three cases, the causative lower dental prosthesis was implant-retained. All affected sublingual caruncles were in close relationship with the implants or the implant bar. Initially, all patients were advised to leave out the lower denture for a period of several weeks. One patient was free of symptoms after this period and did not develop any complaints after adjustment and replacement of the prosthesis. Surgical treatment with posterior rerouting of the orificium of Wharton's duct was performed in the remaining two patients because of persistent signs of obstruction. All patients were free of symptoms after long-term follow-up. Although not frequently occurring, implant-retained dental prostheses seem to play a role in the development of some distally located stenoses of Wharton's duct.